Indian Mutual Fund Industry: Current State and Future Outlook - Gupta, Shivani (Indian Journal of Finance, 2011)
Mutual funds entered into the Indian Capital market. It is growing profitable enough to attract competitors into this cherished territory, encouraging competition among all the mutual fund operators. By 2015, it is expected that the Mutual Fund Industry will grow with Industry AUM growth in the range of 15 to 25 percent from the period 2010 to 2015. But still there are certain loop holes which have to be tackled and some challenges which have to be faced. There is a need to take some strategy to bring more confidence among investors.